Negocjowanie programu nauczania języka obcego z uczniami w Polsce - Sobkowiak, Paweł (Neofilolog, 2019)
This paper aims to explore the rationale of classroom negotiation - understood as a discussion between all participants in the teaching/learning process to decide on the organization of foreign language learning and teaching. It outlines relevant issues connected with the process syllabus and the benefits that can be expected from involving students in classroom decision making. The article presents results of research conducted in Polish schools among both students and teachers at different levels of education in order to see to what extent the foreign language syllabus is negotiated there.